Pre-sleep protein supplementation does not improve performance, body composition, and recovery in British Army recruits (part 1) - Chapman, Shaun; Roberts, Justin; Roberts, Andrew J.; Ogden, Henry; Izard, Rachel; Smith, Lee; Chichger, Havovi; Struszczak, Lauren; Rawcliffe, Alex J. (Frontiers in Nutrition, 2023)
Dietary protein is crucial for optimising physical training adaptations such as muscular strength and mass, which are key aims for athletic populations, including British Army recruits. New recruits fail to meet the recommended protein intake during basic training (BT), with negligible amounts consumed in the evening. This study assessed the influence of a daily bolus of protein prior to sleep on performance adaptations, body composition and recovery in British Army recruits. 99 men and 23 women (mean ± standard deviation [SD]: age: 21.3 ± 3.5 yrs., height: 174.8 ± 8.4 cm, body mass 75.4 ± 12.2 kg) were randomised into a dietary control (CON), carbohydrate placebo (PLA), moderate (20g) protein (MOD) or high (60g) protein (HIGH) supplementation group. Supplements were isocaloric and were consumed on weekday evenings between 2000 and 2100 for 12 weeks during BT. Performance tests (mid-thigh pull, medicine ball throw, 2km run time, maximal push-up and maximal vertical jump) and body composition were assessed at the start and end of BT. Dietary intake, energy expenditure, salivary hormones, urinary nitrogen balance, perceived muscle soreness, rating of perceived exertion, mood and fatigue were assessed at the start, middle and end of BT. Protein supplementation increased protein intake in HIGH (2.16 ± 0.50g⸱kg-1⸱day-1) and MOD (1.71 ± 0.48g⸱kg-1⸱day-1) compared to CON (1.17 ± 0.24g⸱kg-1⸱day-1) and PLA (1.31 ± 0.29g⸱kg-1⸱day-1) (p<0.001). Despite this, there was no impact of supplementation on mid-thigh pull performance (CON=7 ± 19%, PLA=7 ± 19%, MOD=0 ± 16%, HIGH=4 ± 14%) (p=0.554) or any other performance measures (p>0.05). Fat-free mass changes were also similar between groups (CON=4 ± 3%, PLA=4 ± 4%, MOD=3 ± 3%, HIGH=5 ± 4%, p=0.959). There was no impact of protein supplementation on any other body composition or recovery measure. We conclude no benefits of pre-bed protein supplementation to improve performance, body composition and recovery during BT. It is possible the training stimulus was not great, limiting the impact of protein supplementation. However, the high degree of inter-participant variability suggests an individualised use of protein supplementation should be explored, particularly in those who consume sub-optimal (<1.6g⸱kg-1⸱day-1) habitual amounts of protein.